STUDI POTENSI EKSTRAK BRUCEA JAVANICA SEBAGAI BIOAKTIF ANTIKANKER PAYUDARA TERHADAP SEL T47D - Rina Andriyani; Zalinar Udin (Jurnal Kimia Terapan Indonesia, 2010)
research. Buah makasar (Brucea javanica) known has anticancer activity.This research would bioassay the anticancer activity ofBrucea javanica extract toward T47D breast cancercell by in-vitro method, using SRB dyed. In order to study the mechanism, a dot blotting method was carried out to observe the interaction between the Brucea javanica extract with the chromosomal DNA molecule of T47D Cell Line. The interaction results were analyzed with High Performance Liquid Chromatography (HPLC) methods.The result of anticancer activity assay toward T47D cell showed that Brucea javanica extract has activity with IC50 2.69 g/mL, whereas, the interactionresult was analyzed with High Performance Liquid Chromatography (HPLC) methods, exhibited the reduction peaks with the retention time 2.26; 3.63 and 3.94 minutes. It was concluded that the bioactive activity ofBrucea javanica due to the presenceof these candidates.Keyword: Anticancer bioactivity, DNA ofT47D ceIl,